Multidisciplinary approach to diversity and inclusion in the COVID-19-era workplace - Hynes, Rilla J., 1953-; Aquino, Carlos, Jr; Hauer, Josephine, 1961- (Advances in human resources management and organizational development (AHRMOD) book series., 2022)
"This book will provide relevant insight and context in a timely way by creating a knowledge base to work from while leaders and managers continue to work toward diversity and inclusion in the workplace in the current and post-Covid-19 era"--